Comparative Caries Preventive Effects of a Serial Oral Health Counseling Program Versus Routine Oral Hygiene Instruction Provided on Vaccination Visits: A Retrospective Cohort Study in Preschool Children in Nan, Thailand - Rojanaworarit, Dr. Chanapong; Soongswang, Dr. Sureerat; Wipapsathiankul, Sroiphet (Journal of Food Health and Bioenvironmental Science, 2017)
Background: Serial oral health counseling has been locally initiated and implemented in a sub-district health facility without dental professionals in Nan, Thailand; to extend coverage of the counseling service for caregivers of preschool children. Nonetheless, its caries preventive effect, compared to a pre-existing. nationallyimplemented program of oral hygiene instruction on vaccination visits to facilities with affiliated dental personnel, has never been evaluated. Objective: To compare caries preventive effects of serial oral health counseling (index cohort) and routine oral hygiene instruction on vaccination visits (referent cohort) given to caregivers of Thai children aged under 5 in Nan, northern Thailand. Methods: In this retrospective cohort study, two cohorts receiving oral health education service with different patterns were observed. Serial oral health counseling, every 3 months was given to caregivers of 50 children at Health Promoting Hospital, without affiliated dental hygienists, was observed in the index cohort. The referent cohort received oral hygiene instruction and tooth brushing demonstration in a dental model provided on vaccination visits for caregivers of these other 30 children at a hospital with affiliated dental hygienists in another sub-district. The intervention effect was evaluated using multilevel Poisson regression, controlling for sex, age, and baseline caries prevalence, and taking dependency of caries occurrence in individual into account. Results: Caries prevalence at baseline for the index group was 1.99%, while the reference group was caries-free (p=0.090). Caries prevalence at 1-year increased in both groups and a significant difference between groups was determined (9.13% and 5.66%, p= 0.026). After adjustment for sex, age and baseline caries prevalence, a superior caries preventive effect in the index cohort was determined, though it was not statistically significant (adjusted caries prevalence ratio 0.72; 95%CI 0.25, 2.07; p=0.546). A difference in the intervention effect among children of the same cohort was also identified (Random effect: p<0.001). Conclusion: Caries preventive effect of serial oral health counseling program was not inferior to that of oral hygiene instruction on vaccination visits. Serial oral health counseling would therefore be an alternative program in local health facilities without affiliated dental hygienists. Nonetheless, the caries preventive effect of the program might vary according to interpersonal differences.